The Foundations of Scientific Inference : 50th Anniversary Edition - Salmon, Wesley C. (Book collections on Project MUSE., 2017)
"After its publication in 1967, The Foundations of Scientific Inference taught a generation of students and researchers about the problem of induction, the interpretation of probability, and confirmation theroy, Fifty years later, Wesley C. Salmon's book remains one of the clearest introductions to these fundamental problems in the philosophy of science. With this work, Salmon presented a coherent vision of the nature of scientific reasoning, explored the philosophical underpinnings of scientific investigation, and introduced readers to key movements in epistemology and to leading philosophers of the twentieth century, developing his own distinctive views on topics that are still of central importance today. This anniversary edition features an introduction by Christopher Hitchcock, which examines the book's origins, influences, and major themes, its impact and enduring effects, and the disputes it raised, and revisits Salmon's ideas for a new audience of philosophers, historians, scientists, and students."